Cultural Education: Panacea or Amplifier of Existing Inequalities in Political Engagement? - Lea Fobel; Nina Kolleck (Social Inclusion, 2021)
Cultural education has recently been particularly emphasized as key for the promotion of equal opportunities, social cohesion and political engagement. While the relationship between political engagement and formal education has been extensively discussed, little research has been conducted on non‐formal types of education, such as non‐formal cultural education (NCE) in particular. However, the share of NCE programmes is becoming increasingly important as more and more formal institutions are reducing their cultural education programmes. This article examines, firstly, whether NCE actually promotes political engagement and, secondly, who effectively participates in NCE programmes. Using data from the eighth wave (2016–2017) of the German National Educational Panel Study, we implement a mediation analysis within ordered logistic regression models to disentangle the mechanisms at play. Our results indicate that NCE exerts a small but significant effect on political engagement directly and indirectly via political discussions and political interest. However, participation in NCE is strongly influenced by social strata. The advantages of NCE are therefore not evenly distributed across the German population.